Codon bias in the ß-lactam procucer Acremonium chrysogenum - K Jekosch; U Kück (Fungal Genetics Reports, 1999)
In this paper we compile the G/C-content, the codon bias, and consensus sequences for the translation initiation and the intron splicing sites from 19 nuclear genes of the major ß-lactam antibiotic producer Acremonium chrysogenum. Our data are compared with those from other filamentous fungi, such as Aspergillus nidulan, Neurospora crassa, and Sordaria macrospora.